Multimedia Field Test: Can Users Strike Out OCD With the NOCD App?. Issue 1 (February 2020) - Hong, Natalie; Sanchez, Amanda L.; Comer, Jonathan S.
Abstract: NOCD is a mobile application that was developed as an adjunct to evidence-based treatment for individuals diagnosed with OCD. NOCD is not a stand-alone treatment, but rather a resource for patients to access supported strategies outside of treatment sessions. NOCD allows users to assess OCD symptom severity, create exposure and response prevention treatment plans, participate in planned weekly out-of-session exposure exercises, receive guidance during unexpected OCD episodes, share assessment and treatment data, as well as communicate with other NOCD users in an online community. Despite some challenges with initial set-up and inflexibility with varying OCD presentations, we believe this application has strong potential to enhance treatment for patients with OCD. At present, NOCD has not been adequately evaluated in a controlled manner. Although quite promising, research is now needed to examine the extent to which NOCD indeed improves engagement and clinical outcomes relative to traditional evidence-based treatment options. Highlights: NOCD is a free mobile application developed as an adjunct to therapist-delivered treatment for individuals diagnosed with OCD. NOCD offers evidence-based strategies for assessing OCD severity, tracking OCD symptoms and exposures practices, and guiding real-time exposures. Despite incorporation of a number of evidence-based components, the current version has some limitations in regards to ease of use and utility. Research is needed to determine the incremental utility of augmenting traditional therapist-led OCD treatment with NOCD engagement.